1970
DOI: 10.4314/ahs.v19i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of harmful use of alcohol among urban slum dwelling adults in Kenya

Abstract: Background: Harmful alcohol use is a public health problem associated with negative health and socio-economic impacts. However, patterns and dynamics of alcohol use among slum-dwellers in Kenya are poorly understood.Objective: To establish determinants of harmful alcohol use among adults in an urban slum setting in Kenya.Materials and methods: Cross-sectional study involving a consecutively selected sample (N=215) from Githurai, in Nairobi. A pre-tested questionnaire that captured data on socio-demographics, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 87 publications
1
10
2
Order By: Relevance
“…Previous studies in Nairobi, Nakuru and Kericho [ 13 , 14 ] as well as systemic reviews in African region [ 26 , 27 ] have similarly demonstrated that alcohol use is a major risk factor for TB treatment interruption. Of concern is that alcohol is consumed by a group of people often in enclosed places [ 28 ]. This confers a great risk of prolonged community TB transmission since the enclosed places are usually overcrowded and poorly ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Nairobi, Nakuru and Kericho [ 13 , 14 ] as well as systemic reviews in African region [ 26 , 27 ] have similarly demonstrated that alcohol use is a major risk factor for TB treatment interruption. Of concern is that alcohol is consumed by a group of people often in enclosed places [ 28 ]. This confers a great risk of prolonged community TB transmission since the enclosed places are usually overcrowded and poorly ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…Families' alcohol dependence can also contribute. For instance, it was reported that the amount of alcohol consumed by parents and siblings has a significant impact on the amount of alcohol consumed by other siblings [59]. Additionally, having a family history of alcohol use for those with high Barratt Impulsiveness Scale scores (a questionnaire designed to assess the personality/behavioral construct of impulsiveness) was associated with severe alcohol-related consequences [57].…”
Section: Family Background Influencementioning
confidence: 99%
“…In Sub Saharan Africa, Namibia leads on alcohol misuse. The prevalence of alcohol use in Kenya and Uganda is 31.7% and 28.6% respectively (Gitatui, Kimani, Muniu, & Okube, 2019). Moreover, approximately 5.8% of adult males aged between 15-64 years in Kenya have varying levels of alcohol dependency; with 2.4% termed as alcohol abusers (Gitatui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%